Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10661-008-0374-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Benzene on liver functions in rats (Rattus norvegicus)

Abstract: Rats (Rattus norvegicus) were intraperitoneally injected with a 100 mg kg(-1) dosage of benzene, a toxic and carcinogenic agent widely used for industrial purposes. Changes in lactate dehydrogenase (LDH), alkaline phosphatase (ALP), alanine amino transferase (ALT), aspartate amino transferase (AST) activities in serum of rats were investigated at 2, 4, 8, 16, 32, and 64 h following injection. Serum physiological was administered to control group. Activities were measured using autoanalyzer. Benzene caused sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Associated increases in liver size and weight (hepatomegaly) in the exposed animals have also been reported [131]. Several mechanisms contribute to gasolineinduced hepatotoxicity, including the induction of cellular degeneration, downregulation of gene expression, and induction of oxidative stress [132]. Inhibition of CYP2E1, which was recently reported in animals exposed to gasoline vapors [103] is potentially deleterious to the liver.…”
Section: Hepatotoxicitymentioning
confidence: 98%
“…Associated increases in liver size and weight (hepatomegaly) in the exposed animals have also been reported [131]. Several mechanisms contribute to gasolineinduced hepatotoxicity, including the induction of cellular degeneration, downregulation of gene expression, and induction of oxidative stress [132]. Inhibition of CYP2E1, which was recently reported in animals exposed to gasoline vapors [103] is potentially deleterious to the liver.…”
Section: Hepatotoxicitymentioning
confidence: 98%
“…The metabolites of benzene, in addition to adduct formation with DNA and RNA also attach to the proteins of liver, kidney, bone marrow and stomach (Lindstrom et al, 1997;Snyder and Hedli, 1996). Dere and Ari ( 2009) reported that acutely exposed rats at dose 100 mg/kg benzene orally show an increase in the acitivity of hepatic enzymes lactate dehydrogenase (LDH), alkaline phosphatase (ALP), aspartate transaminase ( AST) and alanine aminotransferase (ALT). Another animal study indicated a decrease in P450-2E1 by 34% and induction of glutathione activity by 30% in female CD-1 mice treated with 50 mg/kg benzene for…”
Section: Acute Exposurementioning
confidence: 99%
“…All these workers, in addition to other hydrocarbons, were exposed to benzene at 4.798 mg/m 3 via inhalation. The mechanism for change in the activity of liver enzymes may be related to celluer degenaration, down regulation of gene expression, oxidative stress and related pathways stimulated in hepatocellular cytosols (Dere and Ari, 2009;Davis H. Daiker, 1996).…”
Section: Chronic Exposurementioning
confidence: 99%
“…Exposure to benzene may cause leukemia, lymphoma, multiple myeloma, aplastic anemia, and other solid cancers [2][3][4][5][6]. In addition, benzene exposure is associated with a wide range of non-cancerous but adverse effects including alterations in pulmonary, central nervous system, hematological, hepatic, and renal functions [7][8][9][10][11]. Adverse respiratory effects of benzene include pulmonary edema, acute granular tracheitis, laryngitis, bronchitis, fibrosis, and massive hemorrhaging.…”
Section: Subjectsmentioning
confidence: 99%